Predicting permeability of low-enthalpy geothermal reservoirs: A case study from the Upper Triassic – Lower Jurassic Gassum Formation, Norwegian–Danish Basin. (January 2017) - Weibel, Rikke; Olivarius, Mette; Kristensen, Lars; Friis, Henrik; Hjuler, Morten Leth; Kjøller, Claus; Mathiesen, Anders; Nielsen, Lars Henrik
Highlights: Permeability of shallowly buried sandstones is related to depositional environment. Depositional environment controls grain size, detrital clay content and infrequent early cement. Permeability of deeply buried sandstones varies with burial depth and depositional environment. Ankerite and quartz cement dominate the deeply buried shoreface and lagoonal sandstones. Illite and quartz cement dominate deeply buried fluvial sandstones. Graphical abstract: Abstract: This paper aims at improving the predictability of permeability in low enthalpy geothermal reservoirs by investigating the effect of diagenesis on sandstone permeability. Applying the best fitted porosity–permeability trend lines, obtained from conventional core analysis, to log-interpreted porosity, is crucial in estimating reservoir permeability from logs. Petrographical analysis of sandstones from the Gassum Formation reveals lithological and diagenetic controls on plug permeability and porosity. Porosity–permeability trend lines vary with grain size for the shallowly buried sandstones (<2500 m). Deeply buried sandstones (>2500 m) from a steeply sloping porosity–permeability trend line since the pore-throat diminution due to quartz, ankerite and illite precipitation affects the permeability more than porosity, as evident from mercury injection curves. Permeabilities lower than the general trend for each grain-size group are caused by early diagenetic siderite cement, late diagenetic illitic clays and/or detrital clays. Permeabilities of sandstones deposited under humid well-vegetated conditions in marine and paralic environments, such as the Gassum Formation, are primarily dependent on burial history (maximum burial depth) and depositional environment.